2012
DOI: 10.3357/asem.3239.2012
|View full text |Cite
|
Sign up to set email alerts
|

Oculo-Vestibular Recoupling Using Galvanic Vestibular Stimulation to Mitigate Simulator Sickness

Abstract: When virtual head signals produced by GVS are synchronized to the speed and direction of a moving visual field, manifestations of induced SS in a cockpit flight simulator are significantly reduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 9 publications
1
43
0
Order By: Relevance
“…Techniques for preventing cybersickness include adaptation to VR through repeated exposure (Barrett 2004;Keshavarz 2013), designing VR environments to include stable visual references of the horizon or perceptual vertical (Han et al 2011), developing applications based on physical locomotion (Llorach et al 2014), and providing concurrent vestibular signals by means of galvanic vestibular stimulation (Cevette et al 2012).…”
Section: Is It Possible To Prevent Cybersickness?mentioning
confidence: 99%
“…Techniques for preventing cybersickness include adaptation to VR through repeated exposure (Barrett 2004;Keshavarz 2013), designing VR environments to include stable visual references of the horizon or perceptual vertical (Han et al 2011), developing applications based on physical locomotion (Llorach et al 2014), and providing concurrent vestibular signals by means of galvanic vestibular stimulation (Cevette et al 2012).…”
Section: Is It Possible To Prevent Cybersickness?mentioning
confidence: 99%
“…For instance, Diamond and Markham (1991) found differences in spontaneous ocular torsion between astronauts who experienced sickness during space-flight compared to those who did not. Recent efforts to reduce visual-vestibular cue mismatch in VR support a partial vestibular basis for CS: Both galvanic vestibular stimulation (Cevette et al, 2012;Gálvez-García et al, 2015;Reed-Jones et al, 2007) and bone vibration applied near the vestibular organs (Weech et al, 2018) reduce the level of CS experienced during VR use. There is also a striking similarity between CS symptoms and the symptoms of vestibular labyrinthectomy-although the former are less severe than the latterwith the effects of labyrinthectomy including "nausea and vomiting… excessive perspiration……”
Section: Vestibular Sensitivitymentioning
confidence: 99%
“…GVS was integrated in the simulator program to combine visual and vestibular stimulation (OVR simulation) [for technical details, see Cevette et al ( 2 )]. Visual input was then projected onto a 180° cylindrical screen in front of the subject.…”
Section: Equipmentmentioning
confidence: 99%
“…However, to the best of our knowledge, no studies have evaluated the role of EGG in quantifying the effect of GVS in mitigating SS. We recently showed that the implementation of GVS in a visual fl ight simulator [oculovestibularrecoupled (OVR) stimulation] minimizes the intersensory confl ict that is thought to provoke symptoms such as nausea, vomiting, and dizziness ( 2 ). Therefore, the aims of the current study were: 1) to quantify EGG responses in two groups of subjects during fl ight simulation with or without OVR; 2) to correlate EGG responses with subjective reporting of SS with or without OVR; and 3) to correlate vestibulo-autonomic [cardiac interbeat interval (IBI) or HRV] responses with subjective reporting of SS with or without OVR.…”
mentioning
confidence: 99%